Liturgy and ethics : new contributions from Reformed perspective - Vos, Pieter, 1970- (Studies in Reformed Theology, 2017)
The connection between Christian ethics and liturgy has been on the research agenda for some decades now. Liturgy and Ethics addresses this issue departing from the particularity of the Reformed tradition and its potential for contributing to the discussion. The volume offers in-depth studies of how to understand God's acting in worship, the centrality of justice, and the formative meaning of the liturgy, and relates these reflections to various moral issues and contemporary liturgical practices. In combining a specific theological approach with a broad disciplinary treatment of the topics this volume aims to push forward the scholarly discussion on liturgy and ethics in significant ways.